Specular motion and 3D shape estimation - Dövencioglu, Dicle N.; Ben-Shahar, Ohad; Barla, Pascal; Doerschner, Katja; Justus Liebig University Giessen (My University, 2017)
Abstract Dynamic visual information facilitates three-dimensional shape recognition. It is still unclear, however, whether the motion information generated by moving specularities across a surface is congruent to that available from optic flow produced by a matte-textured shape. Whereas the latter is directly linked to the first-order properties of the shape and its motion relative to the observer, the specular flow, the image flow generated by a specular object, is less sensitive to the object´s motion and is tightly related to second-order properties of the shape. We therefore hypothesize that the perceived bumpiness (a perceptual attribute related to curvature magnitude) is more stable to changes in the type of motion in specular objects compared with their matte-textured counterparts. Results from two two-interval forced-choice experiments in which observers judged the perceived bumpiness of perturbed spherelike objects support this idea and provide an additional layer of evidence for the capacity of the visual system to exploit image information for shape inference.
Keywords: ddc:150